Microstructural evolution in a nanocrystalline Cu-Ta alloy: A combined in-situ TEM and atomistic study. (5th January 2017) - Rajagopalan, M.; Darling, K.; Turnage, S.; Koju, R.K.; Hornbuckle, B.; Mishin, Y.; Solanki, K.N.
Abstract: Under intense heating and/or deformation, pure nanocrystalline (NC) metals exhibit significant grain coarsening, thus preventing the study of length scale effects on their physical response under such conditions. Hence, in this study, we use in-situ TEM heating experiments, atomistic modeling along with elevated temperature compression tests on a thermally stabilized nanostructured Cu–10 at.% Ta alloy to assess the microstructural manifestations caused by changes in temperature. Results reveal the thermal stability attained in NC Cu-10 at.% Ta diverges from those observed for conventional coarse-grained metals and other NC metals. Macroscopically, the microstructure, such as Cu grain and Ta based cluster size resists evolving with temperature. However, local structural changes at the interface between the Ta based clusters and the Cu matrix have a profound effect on thermo-mechanical properties. The lattice misfit between the Ta clusters and the matrix tends to decrease at high temperatures, promoting better coherency. In other words, the misfit strain was found to decrease monotonically from 12.9% to 4.0% with increase in temperature, leading to a significant change in flow stress, despite which (strength) remains greater than all known NC metals. Overall, the evolution of such fine structures is critical for developing NC alloys with exceptional thermo-mechanical properties. Graphical abstract: Highlights: Nanocrystalline Cu-10at.%Ta shows exceptional thermal stability unlike any other NC and ultra-fine grained metals Local structural changes at the interface between nanoclusters and matrix influence the thermo-mechanical properties The evolution of such fine structures is critical for developing nanocrystalline alloys with extreme properties